Enhanced dissolution profiles of glibenclamide with amino acids using a cogrinding method. (March 2021) - Sterren, Vanesa B.; Zoppi, Ariana; Abraham-Miranda, Julieta; Longhi, Marcela R.
Highlights: We propose a simple method for the preparation of binary systems of glibenclamide with the amino acids arginine and serine. Method involves a green process in the preparation of the supramolecular complexes. The combinations obtained allow an enhancement of 90 % in the dissolution of glibenclamide. The physical and chemical stability as well as the cellular toxicity of the drug were not affected by the systems obtained. Abstract: The objective of this work was to improve the dissolution properties of glibenclamide by combining this drug with the amino acids arginine and serine. These binary systems were obtained by solvent-assisted milling. The combinations, physical mixtures and raw compounds were analyzed by using Fourier-transform infrared spectroscopy, powder X-ray diffraction, differential scanning calorimetry, scanning electron microscopy and solid-state nuclear magnetic resonance. In addition, the dissolution profiles of glibenclamide were determined and the factors f1 and f2 were calculated to compare curves. Both systems showed an improvement in their dissolution profiles and proved to be stable under accelerated storage conditions. The combination of glibenclamide and arginine showed the highest dissolution rate. The system also maintains cellular viability in HEK293 T cells. Therefore, this system constitutes an interesting alternative to improving the oral bioavailability of this drug.